Pembuatan Media Promosi E-Catalogue Produk Melalui Bio Instagram Menggunakan Aplikasi Corel Draw Pada Donat Mungil Malang - Dea Oktavia Ilhami; Umi Khabibah; Ahmad Fauzi (Jurnal Ekonomi dan Bisnis Digital, 2025)
Donat Mungil Malang is an MSME (Micro, Small and Medium Enterprises) specializing in the food sector. The types of products sold are various kinds of donuts and tarts. The current promotional media is not adequate to introduce and provide information about its products. The purpose of this research was to create new effective and efficient promotional media in order to provide information on the products being sold. This research used the Action Research method with research procedures consisting of, planning, action, observation and reflection. The data collection methods were observation, interviews, documentation and questionnaires. The measurement of the effectiveness of design as a promotional medium was measured with the EPIC method of Emphaty, Persuasion, Impact and Communication dimensions. The results of the research based on the distribution of questionnaires obtained an average score of EPIC Rate which is very effective, and it is included in the very effective category. It implies that the e-catalogue made has met the criteria of a good e-catalogue. From the results of research on all dimensions that have been calculated using the EPIC method, the highest dimension is the impact dimension with very effective results. Finally, it can be concluded that e-catalogue is very effective to be used as a new promotional media. It is expected that Donat Mungil Malang continues to update the e-catalogue so that online promotion still continues.